Quantitative Analysis of Magnetohdrodynamic Sustained Convective Flow via Vertical Plate - Kirubaharan, D R; Subhashini, A D; Babu, Narendra V.N; Murali, Gundagani (Universitas Sanata Dharma, 2024)
In this paper, the effects of heat and mass transfer on MHD flow in an incompressible, heated fluid that has been accelerated to a steady free stream are investigated. It examines mass movement in a magnetic field as well as heat absorption qualities. In the model, non-linear governing equations and the Laplace transform method are applied. The relationship between temperature, concentration, and velocity and flow parameters is illustrated by studies utilizing parametric data.Keywords: Magnetohdrodynamics, Laplace Transform method, Free Convection, vertical Plate